A Study of cardiac functions in type-2 diabetic patients - Priyambada Panda; Dipti Mohapatra; Sitansu K. Panda; Tapaswini Mishra; Priyadarsini Nibedita; Manasi Behera (International Journal of Medical Research and Review, 2016)
Introduction: The cardiomyopathy in diabetes mellitus (DM) is the disorders in cardiac muscle due to prolonged exposure of vascular tissues to hyperglycemia in DM; and is termed as diabetic cardiomyopathy (DC). The early pre-clinical features of DC are the left ventricular diastolic dysfunction (LVDD), preceding the systolic dysfunction and being able to evolve to symptomatic heart failure.Methods: A cross-sectional study was done including 50 DM-2 patients without any feature of cardiovascular involvement and blood pressure less than 130/80 mmHg. Doppler echocardiography was done to evaluate LVDD.Results: In this study results showed diastolic dysfunction was more common among female than male. The prevalence of diastolic dysfunction is more in cases of longer duration of DM.Conclusion: Our study supports other studies that myocardial damage in DM-2 affects diastolic dysfunction before systolic dysfunction. As Doppler echocardiography is a simple non-invasive procedure to assess cardiac function, so in diabetes it should be done routinely in DM for early diagnosis and prevention of further complications.